A mixed-form solution to the macroscopic elastic properties of 2D triaxially braided composites based on a concentric cylinder model and the rule of mixture. (1st January 2019) - Ye, Wei; Li, Wenbo; Shan, Yongbin; Wu, Jian; Ning, Huiming; Sun, Dongyang; Hu, Ning; Fu, Shaoyun
Abstract: Understanding the elastic properties of 2D triaxially braided composites (2DTBCs) is fundamental for further analysis and design of structural components made from 2DTBCs. Based on a concentric cylinder model (CCM) and the rule of mixture (RoM), we reformulated the global stiffness of 2DTBCs for the anisotropic carbon fiber reinforcement to replace the currently available formulations for the isotropic glass fiber reinforcement with a replacement scheme. First, the global stiffness calculated from CCM, Quek's model and Shokrieh's model was compared for clarification. It was found that Shokrieh's model had the relatively worse performance under the same conditions. Second, the performances of Shokrieh's model, CCM, Quek's model and CCM+RoM (Reuss-type and Voigt-type) were compared using available experiments under various braiding configurations and our experiments on the hybrid carbon/glass fiber reinforced 2DTBCs, which revealed that Quek's model and CCM+RoM (Reuss-type) could yield equivalently great results, and CCM+RoM (Reuss-type) performed even better in some cases.